Pro-B cells sense productive immunoglobulin heavy chain rearrangement irrespective of polypeptide production - Lutz, Johannes; Heideman, Marinus R; Roth, Edith; van den Berk, Paul; Müller, Werner; Raman, Chander; Wabl, Matthias; Jacobs, Heinz; Jäck, Hans-Martin (Proceedings of the National Academy of Sciences - PNAS, 2011)
B-lymphocyte development is dictated by the protein products of functionally rearranged Ig heavy (H) and light (L) chain genes. Ig rearrangement begins in pro-B cells at the IgH locus. If pro-B cells generate a productive allele, they assemble a pre-B cell receptor complex, which signals their differentiation into pre-B cells and their clonal expansion. Pre-B cell receptor signals are also thought to contribute to allelic exclusion by preventing further IgH rearrangements. Here we show in two independent mouse models that the accumulation of a stabilized μH mRNA that does not encode μH chain protein specifically impairs pro-B cell differentiation and reduces the frequency of rearranged IgH genes in a dose-dependent manner. Because noncoding IgH mRNA is usually rapidly degraded by the nonsense-mediated mRNA decay machinery, we propose that the difference in mRNA stability allows pro-B cells to distinguish between productive and nonproductive Ig gene rearrangements and that μH mRNA may thus contribute to efficient H chain allelic exclusion.